A USRP-Based Channel Sounder for UAV Communications - Zhang, Guojin (2020 14th European Conference on Antennas and Propagation (EuCAP), 2020)
The unmanned-aerial-vehicle (UAV) has attracted great interests in both civil and military applications, due to its low cost, flexibility and ability to establish seamless coverage. In this paper, a Universal Software-defined Radio Peripheral (USRP) based channel sounding system for characterizing the UAV communication channel is introduced, which can be applied in both active and passive measurement campaigns. To investigate the effect of the equipment in the UAV measurement system, measurements were conducted by connecting two USRP devices directly with a cable. Furthermore, a post-processing method is proposed to calibrate the delay shift and “fake” Doppler frequency caused by the frequency deviation of the local oscillator in the system.<br
Keywords: Local oscillators; Position measurement; Real-time systems; Rail transportation; Frequency measurement; Delays; Doppler effect; unmanned-aerial-vehicle (UAV); channel sounding; delay shift; “fake” Doppler frequency; unmanned-aerial-vehicle (UAV); channel sounding; delay shift; and; fake; Doppler frequency